Parteneriatul cu mediul de afaceri – soluţia pentru succesul învăţământului profesional şi tehnic. Studiu de caz: școala profesională eurobusiness Oradea - Stănilă, Gabriel (Calitatea Vieții, 2016)
In the last years, Romania is confronting a crisis of qualified labour force (highschool studies), one of the causes being the decline of professional learning. One solution of increasing the efficiency of professional learning system is given by the partnership between school and business environment as so the school responds better to the economy needs, regarding qualifications and competencies it forms. Eurobusiness Professional School of Oradea represents a good example of technical school which shows a strong connection between business environment and school itself.